Stress fracture of the lower limbs in athletes - Migliorini, S. (Science + Triathlon 2015 World Conference, 2015)
Stress fracture are a common cause of injury in runners and triathletes. There is a spectrum of bone response to repetitive stress: normal response, stress reaction and stress fracture. Physicians and health care providers should maintain a high index of suspicion for stress fracture in runners presenting with insidious onset of focal bone tenderness associated with recent changes in training intensity or regimen. Imaging, particularly MRI, is often utilized to supplement the history and physical examination. Poor training technique and a variety of extrinsic and intrinsic factors, including REDs, may predispose runners to stress fractures. To provide treatments and prognostic parameters it is important to classify stress fractures as high risk versus low risk based on the anatomic location of the fracture and the natural history of fractures occurring at this anatomic site. It is particularly important to recognize «high-risk» fractures, as these are associated with an increased risk of complication. Accurate and timely diagnosis and treatment are essential in the care of the athlete with stress fracture. The best form of treatment for stress fracture is prevention. Any contributing factors, such as biomechanical abnormalities, anatomy, gender, nutrition, equipment and running terrain, should be addressed.